A Head-to-Head Comparison of Three Self-Help Techniques to Reduce Body-Focused Repetitive Behaviors. Issue 4 (July 2022) - Moritz, Steffen; Penney, Danielle; Ahmed, Kaser; Schmotz, Stella
Body-focused repetitive behaviors (BFRBs) include skin picking, trichotillomania, nail biting and cavitadaxia/lip-cheek biting, among other behaviors. For the first time, we compared three different self-help techniques aimed at reducing BFRBs. We explored the acceptance and preliminary efficacy of the approaches and whether the techniques exerted differential effects depending on BFRB-type. A total of 113 participants with at least one BFRB were randomly allocated to either habit reversal training (HRT; active elements: awareness and competing response training), decoupling (DC) or decoupling in sensu (DC-is). Reassessment was conducted 4 weeks later. The Generic Body-Focused Repetitive Behavior Scale (GBS) served as the primary outcome. The completion rate was best for DC-is (68.6%) as compared to HRT (57.1%) and DC (53.5%). A total of 34.8% of completers in the DC group showed an improvement of at least 35% on the GBS compared to 10.0% in the HRT and 23.3% in the DC-is group. In accordance with previous work, moderator analyses showed that improvement under DC is best for non-skin-pickers. A dose-effect relationship emerged, particularly for HRT. Subjective appraisal ratings were more favorable for DC-is and HRT than for DC. With respect to completion rate, subjective appraisal and symptom improvement, DC-is yielded consistently satisfactory results, whereas HRT showed good subjective but rather poor objective improvement. Those who performed DC, especially non-skin-pickers, showed good improvement but overall completion and subjective efficacy were low. Future studies should investigate whether the three techniques exert add-on effects when combined and whether demonstration via new media (e.g., video) will augment comprehensibility and thus efficacy of the techniques.